Development of images to braille conversion software for alphabets using template matching and rule based - Izzati Farrahiyah, Mazlan (2011)
An images to Braille Conversion Software/Hardware (Alphabets) is a system that helps Blind people to read available reading materials.The current system only can support uppercase English alphabets from A to Z using six dots.Hence,to complete the current system,we have developed a complete images to Braille conversion system to process and convert the images of normal texts into Braille dots (8 dots) taking into account (i) lower/upper case English alphabets,(ii) numbers and (iii) special characters/symbols all together.Particularly,this research focuses on the part one,which is the processing and conversion of lower/upper case alphabets.This system receives the input images,process and compares it with characters templates that have been stored in the database. The processing of images is done into five steps systematically as (i) binaiization and pixel inversion,(ii) noise removal.(iii) segmentation and clustering, iv)line identification and finally (v) character extraction.A Gill is develop to observe the processes and displayed Braille dots to ensure the accuracy.Followed by a hardware is develop to demonstrate the working ability to display the Braille dots in terms LED.This system is targeted to integrate with Numbers and Special Characters and then use with hand phone or camera as a handy plug-in/plug-out device.So that the Blind people can carry it anywhere anytime with them to capture picture and make it readable for them.They also will be able to read the received SMS in their hand phone.The system also will read the material aloud for additional convenience for this group of people so that they can read and listen as per need.The developed integrated system may offer a easy life for the Blind community by widening the reading materials in a affordable and convenient way.